Understanding B Corporations as agents of strategic sustainability: a meta-aggregative review - Alarcón Arguello, Oscar Julian; Güiza Pinzón, Fabian David; Sarmiento Rojas, Jorge Andres (Frontiers in Sustainability, 2026)
This study analyzes B Corporations as emerging agents of strategic sustainability in Ibero-America, where they function not only as hybrid business models but also as institutional responses to persistent socio-environmental and governance gaps. The research explores how B Corps articulate purpose-driven management through governance structures, innovation processes, impact verifiability, and stakeholder legitimacy, positioning themselves as alternatives to the fragmented logic of traditional CSR. Using a Systematic Literature Review (PRISMA 2020) combined with a meta-aggregative synthesis (JBI), the study integrates diverse theoretical and empirical contributions to identify the conceptual patterns that define the functioning and hybrid purpose of the B Corp/BIC model in the region, which constitutes the central objective of the research: to analyze how the B Corp/BIC model is implemented and legitimized in Ibero-America by identifying the conceptual patterns that shape its functioning and hybrid purpose. The synthesis reveals six recurring categories, with governance emerging as the central axis that connects innovation, trust-building, and measurable impact. A significant finding is the persistent disconnect between the theoretical alignment of B Corporations with circular economy principles and their limited explicit incorporation in current literature, which constrains their regenerative potential. The conclusions suggest that B Corps act as catalytic nodes capable of compensating for institutional deficits and enabling more robust sustainability transitions in emerging economies; however, this transformative capacity remains contingent on embedding circular strategies into their operational protocols.